1965
DOI: 10.3758/bf03343255
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral effects of isolation in the rat

Abstract: Ab.traetMale albino rats were raised either invidually (N = 13) or in groups (N = 12) from weaning at 21 days of age until they were tested at 111 days of age. Experimenter ratings and a "timidity" test showed the isolated Ss to be more emotional than group-raised Ss. No significant differences were found on startle or activity tests. ProbleDlAccording to Hatch et al (1963), after being housed for three months in an individual cage, "the isolated rat is a nervous, aggressive intractable animal." Objective test… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
11
0

Year Published

1966
1966
2003
2003

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(13 citation statements)
references
References 5 publications
2
11
0
Order By: Relevance
“…Previous studies have reported conflicting results: Stern et al (1960), Thiessen et al (1962), Thiessen (1963), and Moyer & Korn (1965) all showed that group-housing leads to an increase in open field activity compared with isolation. The reverse was found by Essman (1966) and Weltman et al (1966).…”
mentioning
confidence: 87%
See 1 more Smart Citation
“…Previous studies have reported conflicting results: Stern et al (1960), Thiessen et al (1962), Thiessen (1963), and Moyer & Korn (1965) all showed that group-housing leads to an increase in open field activity compared with isolation. The reverse was found by Essman (1966) and Weltman et al (1966).…”
mentioning
confidence: 87%
“…Besides providing evidence concerning the possible role of social factors in population control (Chrlstian & Davis, 1964;Thiessen, 1964), this area of research has stimulated interest from workers more concerned with experimental psychology (e.g., Essman, 1966Essman, , 1968Moyer & Korn, 1965). The latter approach is characterized by investigations which sacrifice simulation of the natural environment for a greater degree of experimental control, and by theoretical discussions which consider the mechanisms involved in the response of the dependent variables to differences in the social environment (e.g., Welch, 1964).…”
mentioning
confidence: 99%
“…Isolation-reared rats show excessive reactivity to handling (Ader, Kreutner, & Jacobs, 1963;Hatch, Balazs, Wiberg, & Grice, 1963), increased timidity (Moyer & Korn, 1965), and enhanced emotionality (DaSilva, Ferreira, Carobrez, & Morato, 1996;Koch & Arnold, 1972). These phenomena are referred to as ''the isolation stress syndrome'' (Hatch et al, 1965;Holson, Scallet, Ali, & Turner, 1991).…”
mentioning
confidence: 99%
“…Rats reared in social isolation after weaning have been considered as an animal model of chronic stress since isolation rearing could be an experience that is an ecologically unnatural situation for this species (Moyer & Korn, 1965). Isolation-reared rats show excessive reactivity to handling (Ader, Kreutner, & Jacobs, 1963;Hatch, Balazs, Wiberg, & Grice, 1963), increased timidity (Moyer & Korn, 1965), and enhanced emotionality (DaSilva, Ferreira, Carobrez, & Morato, 1996;Koch & Arnold, 1972).…”
mentioning
confidence: 99%
“…In short, it is not clear under what circumstances social facilitation occurs and what influence it may have on learning and stress. Moyer & Korn (1965), for instance, have shown that isolated albino rats are more emotional than group-raised Ss. Open field tests have also revealed that isolated Ss are more emotional than group-housed rats (Hahn, 1965).…”
mentioning
confidence: 99%